Chemical Composition and Antimicrobial Activities of the Essential Oil From Salvia mirzayanii Leaves. (October 2017) - Zomorodian, Kamiar; Moein, Mahmoodreza; Pakshir, Keyvan; Karami, Forough; Sabahi, Zahra
Resistance of many pathogens to available drugs is a global challenge and is leading to growing interest in natural alternative products. In this study, chemical composition and in vitro antibacterial and antifungal activities of the essential oil from Salvia mirzayanii were investigated. The chemical constituents of essential oil from S mirzayanii were analyzed by gas chromatography–mass spectrometry. The antimicrobial activity was determined by broth microdilution. The main identified compounds were 1, 8-cineole (41.2 ± 1.3%), linalool acetate (11.0 ± 0.5%), and α-terpinyl acetate (6.0 ± 0.4%) (mL of essential oil/g of plant material). The MIC95 were 0.03 to 0.5 µL/mL and 16 to 128 µL/mL for gram-positive and gram-negative bacteria, respectively. These results indicated that Salvia mirzayanii essential oil significantly inhibited the growth of standard and clinically isolated tested yeasts by MIC50 0.03 to 1 µL/mL. Potent antibacterial and antifungal activities of Salvia mirzayanii essential oil may be considered in future study, particularly against antibiotic-resistant cases.